PELATIHAN BINA ORANG TUA SEBAGAI UPAYA PENINGKATAN LITERASI PERKEMBANGAN ANAK USIA DINI KEPADA ORANG TUA - Aziz, Ahmad Abdul; Bahfen, Munifah (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
Parent Guidance Training (BOT) is one of the programs designed by Pos Paud Sahabat Karawang as an effort to answer issues, especially those related to early childhood development (AUD) that are currently occurring in the field (in this case, at Paud Sahabat Karawang school). The theme of the Parent Guidance Training (BOT) was raised based on observations and the need to solve problems of early childhood development and education, both from the context of physical, cognitive, socio-emotional development, educational dynamics, and so on. The speakers who were presented as resource persons in this activity were academics and practitioners in the fields of early childhood education, health and psychology. Based on the results of the analysis, it was concluded that the Parent Guidance Training (BOT) with the theme